IMPROVING THE SYSTEM OF EARLY DETECTION OF ENDOCRINE DISEASES IN PRIMARY HEALTHCARE INSTITUTIONS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Endocrine diseases such as diabetes mellitus, thyroid disorders, obesity, and metabolic syndrome are among the most prevalent non-communicable conditions worldwide, contributing significantly to morbidity, mortality, and healthcare costs. Despite their growing burden, many cases remain undiagnosed until advanced stages, leading to complications that could have been prevented through timely intervention. Primary healthcare institutions, as the first point of contact for most patients, play a critical role in the early detection and management of these disorders. However, current systems often face challenges including limited screening protocols, insufficient physician training, inadequate laboratory infrastructure, and low public awareness. This study emphasizes the importance of strengthening early detection mechanisms within primary healthcare by introducing standardized screening guidelines, enhancing the capacity of healthcare providers through continuous medical education, and integrating digital health technologies such as electronic health records and mobile applications for risk monitoring. Furthermore, community-based awareness campaigns and improved laboratory support are highlighted as essential components of a comprehensive strategy. By implementing these measures, healthcare systems can achieve earlier diagnosis, reduce the incidence of complications, and improve patient outcomes while lowering long-term costs. Ultimately, the improvement of early detection systems for endocrine diseases at the primary healthcare level represents a vital step toward building resilient health systems capable of addressing the growing burden of non-communicable diseases in both urban and rural populations.
Keywords: Endocrine diseases; early detection; primary healthcare; diabetes mellitus; thyroid disorders; metabolic syndrome; screening protocols; digital health; public awareness; healthcare systems.